Leakage effects in natural resource supply chains: a case study from the Peruvian commercial charcoal market - Bennett-Curry, A.; Malhi, Y; Menton, M. (Informa UK Limited, 2013)
Wood charcoal is generally viewed as a rudimentary form of energy. It is often understood in terms of its role of providing rural poor populations with basic energy needs, and/or the contribution its production makes to local forest degradation. More recently, the potentially much larger impact of urban demands on natural resources is attracting attention. Rural/urban supply chains are becoming an important research focus as nations try to start aligning with international environmental agreements by providing more honest environmental data regarding deforestation and associated emissions. This paper presents results from quantitative and qualitative research investigating the commercial charcoal supply chain servicing the metropolitan area of Lima, the capital of Peru. Long-term conservation initiatives protecting the species algarrobo (Prosopis spp.) were found to have caused a leakage effect in which the species shihuahuaco (Dipteryx spp.) from the Amazon region of Ucayali is compensating for the reduced production of algarrobo charcoal. Charcoal production in the urban area of Pucallpa, Ucayali is estimated to be more than eighty times the official figures, the vast majority of which goes to service the thousands of chicken brasseries in Lima. Commercial Amazonian charcoal is produced predominantly from sawmill by-product, and thus not found to be a direct threat to the rainforest. However, reduced availability of the by-product of the preferred species shihuahuaco to charcoal producers raises concern that this species is being heavily overexploited in the region.